2021
DOI: 10.3390/catal11111299
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Hydrogenolysis to Produce 1,2-Propanediol in Absence of Molecular Hydrogen Using a Pd Promoted Cu/MgO/Al2O3 Catalyst

Abstract: The catalytic process of glycerol hydrogenolysis to produce 1,2-propandiol (1,2-PD) in the absence of external hydrogen addition has been investigated. The methanol present in the crude glycerol from a biodiesel production process is used to provide in situ hydrogen produced via methanol steam reforming for the glycerol hydrogenolysis process. This process can reduce the additional cost for the transportation and storage of molecular hydrogen and also reduce the safety risks related to using high hydrogen pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…When the hydrogen pressure is reduced, the promoting effect of Pd becomes more obvious. Furthermore, the selectivity of EG using the 2Pd/CZA catalyst is higher than that using the CZA catalyst, suggesting a promoting effect of the catalytic activity for the C-C cleavage of glycerol caused by the introduction of Pd, which has been reported in a number of works [4,21,29,41]. In general, it is found that when the glycerol hydrogenolysis reaction is carried out under a high hydrogen pressure (i.e., 2.76 Mpa), the addition of Pd is not necessary, as Pd is an expensive metal compared with copper, and the promoting effect of Pd is not significant.…”
Section: Equations Of Materials Balancesmentioning
confidence: 65%
See 1 more Smart Citation
“…When the hydrogen pressure is reduced, the promoting effect of Pd becomes more obvious. Furthermore, the selectivity of EG using the 2Pd/CZA catalyst is higher than that using the CZA catalyst, suggesting a promoting effect of the catalytic activity for the C-C cleavage of glycerol caused by the introduction of Pd, which has been reported in a number of works [4,21,29,41]. In general, it is found that when the glycerol hydrogenolysis reaction is carried out under a high hydrogen pressure (i.e., 2.76 Mpa), the addition of Pd is not necessary, as Pd is an expensive metal compared with copper, and the promoting effect of Pd is not significant.…”
Section: Equations Of Materials Balancesmentioning
confidence: 65%
“…It was proven both mathematically and experimentally in our previous work that the reactions were carried out in the absence of external liquid-to-solid mass transfer limitation under the current reaction conditions [3,29]. In addition, the reactions were also mathematically verified to be absent from intraparticle diffusion limitation [29,30]. Therefore, all the reactions were in the kinetic control regime.…”
Section: Catalytic Activity Testmentioning
confidence: 79%
“…The introduction of Pd could improve the glycerol conversion and 1,2-PD selectivity by enhancing the hydrogenation of acetol. Meanwhile, the study proved that glycerol concentration influenced the 1,2-PD selectivity greatly, and higher glycerol concentration led to lower 1,2-PD selectivity [4].…”
mentioning
confidence: 94%
“…Ng. et al applied a Pd-promoted Cu/MgO/Al 2 O 3 catalyst for the hydrogenolysis of glycerol to 1,2-propandiol (1,2-PD) using in situ hydrogen source provided by the reforming of methanol [4]. The introduction of Pd could improve the glycerol conversion and 1,2-PD selectivity by enhancing the hydrogenation of acetol.…”
mentioning
confidence: 99%
“…Catalysts such as Ru, Pt, Ni, and Mo are expensive but offer the possibility of conducting hydrogenolysis and aqueous phase reforming (APR) at temperatures below 250 °C, which have a positive effect on selectivity. 37 Noble metals must balance cleavage of the C−C bond and selective hydrogenolysis of glycerol. Torres et al found that the selectivity of 1,2-propanediol using the Pt/Al 2 O 3 catalyst was better in situ than with an external hydrogen source.…”
Section: ■ Introductionmentioning
confidence: 99%